Detection of canine anti-DEA 1 antibodies using flow cytometry in dogs following DEA 1-positive blood transfusion - Santos, Suzana Claudia Spinola dos; Moroz, Ludmila Rodrigues; Santos, Mariane Melo dos; Santos, Allan Souza dos; Trindade, Soraya Castro; Meyer, Roberto; Costa, Maria de Fátima Dias (Brazilian Journal of Veterinary Research and Animal Science, 2018)
The shortage of dog blood donors in veterinary emergencies can lead to blood transfusions between animals whose blood type has not been identified. The antibody profile serves as a warning sign for animals that require a second blood transfusion, which is only advisable from compatible donor dogs. This article focuses on determination of anti-DEA 1 antibodies using the flow cytometry technique in dogs that have undergone a transfusion using DEA 1-positive blood, compared to results obtained from crossmatching. Blood from 18 DEA 1-positive donors ranked according to the chromatographic technique was used to transfuse thirty-three animals with unknown blood types and which demonstrated negative crossmatching to donors. On post-transfusion days 7, 14, 21 and 28, 45% and 27% of the animals tested positive for the anti-DEA 1 antibody, through crossmatching and flow cytometry, respectively. Detecting antibodies using the flow cytometric technique has high specificity and sensitivity, while crossmatching methods are highly sensitive but manifest low specificity. Following blood transfusion, animals that did not present as positive through crossmatching or flow cytometry were considered different from all other DEA 1-positive blood groups.